Proyecto de evaluación sobre una plan de operaciones e información turística de la ruta del sol desde una plataforma virtual en la provincia de Santa Elena - Dillon Pazmiño, Douglas Alberto (2010)
In the present Project we will develop a marketing study, located in the coastal area between Salinas and National Park Machalilla, also known as the Route of the sun, which because of its geographical characteristics complement with each other, once we found the problems and information leaks related to the marketing of the destiny, we will apply the basic principles of e commerce, so the burocratic system will be optimize, improving the management of the destiny. Besides developing an effective system of communication, we will design a manual of politics and general schedule that will be useful tools in the management field, in the communication field, and in the forecasting of touristic flow, which are important elements in the touristic planning, all this will be done taking in consideration the sustainable development of the region.